Stress among medical students in Poland - Brożyna, Klaudia; Radzka, Agnieszka; Tkaczyk, Jędrzej; Ciechański, Krystian; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2018)
There is no doubt that stress is bonded with daily routine of students. Medical colleges are one of these environments, which are associated with negative impact of stress on many fields of life like physical health, academic feedback and physiological mood of student`s. Aim of study is to analyse the incidence of stress among students from different fields of study in Medical Universities in Poland. In that case we perform anonymous questionnaire, which contained 23 original questions and was widespreaded via Internet. Stress is a common problem among students from medical faculties. There is no doubt that stress is an inseparable companion during not only studies, but also after degree while working as a professional. For that reason it is necessary to encourage young people to find their own effective manner to cope with stress.